Deciphering the impact of parameters influencing transgene expression kinetics after repeated cell transduction with integration‐deficient retroviral vectors. (27th February 2015) - Schott, Juliane W.; Jaeschke, Nico M.; Hoffmann, Dirk; Maetzig, Tobias; Ballmaier, Matthias; Godinho, Tamaryin; Cathomen, Toni; Schambach, Axel
Abstract: Lentiviral and gammaretroviral vectors are state‐of‐the‐art tools for transgene expression within target cells. The integration of these vectors can be deliberately suppressed to derive a transient gene expression system based on extrachromosomal circular episomes with intact coding regions. These episomes can be used to deliver DNA templates and to express RNA or protein. Importantly, transient gene transfer avoids the genotoxic side effects of integrating vectors. Restricting their applicability, episomes are rapidly lost upon dilution in dividing target cells. Addressing this limitation, we could establish comparably stable percentages of transgene‐positive cells over prolonged time periods in proliferating cells by repeated transductions. Flow cytometry was applied for kinetic analyses to decipher the impact of individual parameters on the kinetics of fluoroprotein expression after episomal retransduction and to visualize sequential and simultaneous transfer of heterologous fluoroproteins. Expression windows could be exactly timed by the number of transduction steps. The kinetics of signal loss was affected by the cell proliferation rate. The transfer of genes encoding fluoroproteins with different half‐lives revealed a major impact of protein stability on temporal signal distribution and accumulation, determining optimal retransduction intervals. In addition, sequential transductions proved broad applicability in different cell types and using different envelope pseudotypes without receptor overload. Stable percentages of cells coexpressing multiple transgenes could be generated upon repeated coadministration of different episomal vectors. Alternatively, defined patterns of transgene expression could be recapitulated by sequential transductions. Altogether, we established a methodology to control and adjust a temporally defined window of transgene expression using retroviral episomal vectors. Combined with the highly efficient cell entry of these vectors while avoiding integration, the developed technology is of great significance for a broad panel of applications, including transcription‐factor‐based induced cell fate conversion and controlled transfer of genetically encoded RNA‐ or protein‐based drugs. © 2015 International Society for Advancement of Cytometry